2016
DOI: 10.1088/0741-3335/58/4/044006
|View full text |Cite
|
Sign up to set email alerts
|

Scrape-off layer turbulence in TCV: evidence in support of stochastic modelling

Abstract: Abstract. Intermittent fluctuations in the TCV scrape-off layer have been investigated by analysing long Langmuir probe data time series under stationary conditions, allowing calculation of fluctuation statistics with high accuracy. The ion saturation current signal is dominated by the frequent occurrence of large-amplitude bursts attributed to filament structures moving through the scrape-off layer. The average burst shape is well described by a double-exponential wave-form with constant duration, while the w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
97
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(115 citation statements)
references
References 69 publications
(182 reference statements)
16
97
2
Order By: Relevance
“…The case of a one-sided exponential pulse function is readily generalized to a pulse shape that is continuous by introducing a finite pulse rise time, 79,82,88 …”
Section: B Two-sided Exponential Pulsementioning
confidence: 99%
See 1 more Smart Citation
“…The case of a one-sided exponential pulse function is readily generalized to a pulse shape that is continuous by introducing a finite pulse rise time, 79,82,88 …”
Section: B Two-sided Exponential Pulsementioning
confidence: 99%
“…[78][79][80][81][82][83][84] From single-point measurements it has been demonstrated that there is an exponential distribution of both the peak amplitudes and the waiting times between them. Moreover, the average duration time does not depend on the amplitude and also appears to be robust against changes in plasma parameters.…”
Section: Introductionmentioning
confidence: 99%
“…The statistical properties of these bursts in the SOL of several tokamak plasmas have recently been elucidated by the analysis of long data time series from probe measurements and gas puff imaging. [11][12][13][14][15] Conditional averaging has revealed exponentially distributed burst amplitudes and waiting times, while the burst duration is found to be constant. The wave-form for largeamplitude bursts in the time series is well described by an exponential function.…”
Section: Introductionmentioning
confidence: 97%
“…[6][7][8][9][10] The average SOL plasma density and the particle and heat fluxes due to the radial motion of plasma filaments depend on their velocity, amplitude, and frequency of occurrence. [11][12][13][14][15] The turbulence-driven transport results in broad plasma profiles in the SOL and enhanced levels of plasma--wall interactions that may be an issue for the next generation plasma confinement experiments and future fusion power reactors. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] The radial motion of blob-like structures leads to largeamplitude bursts in single-point measurements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation